2010
DOI: 10.1080/10803548.2010.11076854
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Technology of Personal Heating Garments

Abstract: energy save cold protection personal heating garment (PHG) human comfort

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(77 citation statements)
references
References 41 publications
(41 reference statements)
0
73
0
1
Order By: Relevance
“…11,51 The fast response of PEDOT/PSS fibers is ascribed to the small diameter and a direct measurement without any substrate attached to the fibers. To summarize, the merit of PEDOT/PSS fibers as heaters lies in (1) very fast response which is comparable with metal wires; (2) low density, high conductivity, high flexibility, stretchability and better tolerance to frequent bending and contact as compared to carbon fibers and metallic wires 54 ; and (3) good spinnability for directly co-spinning with nonconductive polyester fibers from different nozzles, which can be easily twisted and woven into textiles for the application of wearable heaters.…”
Section: Electrothermal Responsementioning
confidence: 99%
See 1 more Smart Citation
“…11,51 The fast response of PEDOT/PSS fibers is ascribed to the small diameter and a direct measurement without any substrate attached to the fibers. To summarize, the merit of PEDOT/PSS fibers as heaters lies in (1) very fast response which is comparable with metal wires; (2) low density, high conductivity, high flexibility, stretchability and better tolerance to frequent bending and contact as compared to carbon fibers and metallic wires 54 ; and (3) good spinnability for directly co-spinning with nonconductive polyester fibers from different nozzles, which can be easily twisted and woven into textiles for the application of wearable heaters.…”
Section: Electrothermal Responsementioning
confidence: 99%
“…3g and h), which is a comfortable temperature range for hands (between 33 and 38 C). 41,54 Smaller power sources, such as coin batteries, could also be used, but the location of the electrodes, the conductivity and the arrangement of the fiber bundle on the glove would need to be engineered.…”
Section: Electrothermal Responsementioning
confidence: 99%
“…Inner clothing, more difficult to visually assess plays a major role in moisture absorption and sweat evaporation, and directly affects the subjective assessment of the thermal environment and consequently the thermal comfort. (Wang, Gao, Kuklane & Holmer, 2010) proposes a possible solution to the current rule of thumb estimation of clothing insulation level. It is the recently emerging heating garments equipped with smart technology and fabric.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wang et al summarized advantages and disadvantages of several kinds of personal heating garments. 3 Ozan et al 4 developed heating garment by using steel-based conductive yarns with portable power supplies and controlling electric circuit and evaluated the performances of the heating garments on a thermal mannequin in cold weather environments. In another study the authors showed that performances of the heating fabric were closely correlative with power supply and current amount.…”
Section: 2mentioning
confidence: 99%